2000
DOI: 10.1046/j.1537-2995.2000.40020245.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the newly described human circovirus, TTV, in United States blood donors

Abstract: Evidence of infection or exposure to TTV appears to be common among blood donors in United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 25 publications
6
49
2
2
Order By: Relevance
“…Furthermore, as TTV classification is based on the ORF1 sequences, our initial attempts to classify all of our TTV sequences and match them with the ORF2 antibody data were concluded to be futile. In all, our TTV DNA prevalence among seroconverted and seroreverted children is in line with those reported in previous studies, showing TTVs to circulate commonly in the general population irrespective of the antiviral antibodies (Handa et al, 2000;Kakkola et al, 2008;Ott et al, 2000) and highlighting the remarkable ability of these viruses to evade immunity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, as TTV classification is based on the ORF1 sequences, our initial attempts to classify all of our TTV sequences and match them with the ORF2 antibody data were concluded to be futile. In all, our TTV DNA prevalence among seroconverted and seroreverted children is in line with those reported in previous studies, showing TTVs to circulate commonly in the general population irrespective of the antiviral antibodies (Handa et al, 2000;Kakkola et al, 2008;Ott et al, 2000) and highlighting the remarkable ability of these viruses to evade immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Thus far, only a few studies have addressed TTV antibodies, by employing methods such as immunoblotting, immunoprecipitation and immunocapture PCR (Handa et al, 2000;Kakkola et al, 2008;Ott et al, 2000;Tsuda et al, 1999Tsuda et al, , 2001). Because of small-sized study groups or methodological limitations, the seroprevalence assessments call for reappraisal.…”
Section: Introductionmentioning
confidence: 99%
“…ORF1 N and C terminus specific antibodies have also been detected in the blood of infected individuals [103,104]. TTV immunocomplexes have been detected in the sera of TTV positive individuals [102,105].…”
Section: Ttv Immunologymentioning
confidence: 98%
“…For example, Takahashi et al (1998), using T801/T935 primers, found a prevalence of 92% in Japanese blood donors, compared to the 12% previously found with the use of NG059/NG061/NG063 primers ). Among US blood donors, prevalences of 1-8%, 34%, and 42% have been reported, using the NG059/ NG061/NG063 (Charlton et al 1998, Handa et al 2000, BF1/BR1/BF2/BR2 (set 2) , and T801/T935 (Handa et al 2000) sets of primers, respectively. The present study was initiated to assess the prevalence of TTV infection in a population visiting a general hospital in the south of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Very high seroprevalences (30-93%) of TTV have been found in normal healthy populations from different parts of the world, including developed and developing countries (Prescott & Simmonds 1998, Tanaka et al 1998, Okamoto et al 1999, Handa et al 2000. In several other studies, however, the true TTV prevalence has been greatly underestimated due to the use of PCR primers and/or protocols that did not allow the successfull amplification of DNAs from all the isolates.…”
mentioning
confidence: 99%